Highly crystalline vanadium phosphate catalysts synthesized using poly(acrylic acid-co-maleic acid) as a structure directing agent. Issue 9 (10th September 2015) - Alhumaimess, Mosaed; Lin, Zhongjie; Dummer, Nicholas F.; Taylor, Stuart H.; Hutchings, Graham J.; Bartley, Jonathan K.
Abstract : Addition of poly(acrylic acid-co-maleic acid) (PAAMA) during the synthesis of vanadium phosphates changes the morphology and improves the catalyst performance. Abstract : Vanadium phosphate catalysts have been widely studied for the selective oxidation of alkanes to a variety of products, including maleic and phthalic anhydride. More recently they are starting to find use as low temperature liquid phase oxidation catalysts. For all these applications the synthesis of the precursor is key to the performance of the final catalyst. Changes in the preparation procedure can alter the morphology, surface area, crystallinity, oxidation state and the phases present in the final catalyst which can all affect the selectivity and/or activity of the catalyst. Adding a diblock copolymer, poly(acrylic acid-co-maleic acid) (PAAMA), during the synthesis was found to influence the crystallinity and morphology of the VOHPO4 ·0.5H2 O precursors obtained. An optimal level of copolymer was found to form precursors that showed a faster, more efficient, activation to the active catalyst, whereas high amounts of copolymer formed thin platelets, which were prone to oxidise to undesirable V 5+ phases under reaction conditions, reducing the selectivity to maleic anhydride.